2016
DOI: 10.3892/ol.2016.4104
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular adhesion molecule 1 is a sensitive and diagnostically useful immunohistochemical marker of papillary thyroid cancer (PTC) and of PTC-like nuclear alterations in Hashimoto's thyroiditis

Abstract: Intercellular adhesion molecule 1 (ICAM-1) is important in the progression of inflammatory responses. Recently, increased levels of ICAM-1 have been reported in a number of types of malignancy. The present study aimed to investigate ICAM-1 expression in papillary thyroid cancer (PTC) and in Hashimoto's thyroiditis (HT) with PTC-like nuclear alterations, and to assess the predictive value of ICAM-1 in thyroid lesions. ICAM-1 expression was retrospectively investigated in 132 consecutive cases of PTC, 72 cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…This feature may be an important factor in the progression of cancer of the thyroid gland. Similar work was reported by Zhang et al that ICAM1 expression is upregulated in PTC (Papillary Thyroid Cancer) and in HT (Hashimoto's disease) [10]. Buitrago et al showed that ICAM1 was upregulated in PTC at the levels of both gene and protein expression.…”
Section: Thyroid and Role Of Cytokinessupporting
confidence: 77%
“…This feature may be an important factor in the progression of cancer of the thyroid gland. Similar work was reported by Zhang et al that ICAM1 expression is upregulated in PTC (Papillary Thyroid Cancer) and in HT (Hashimoto's disease) [10]. Buitrago et al showed that ICAM1 was upregulated in PTC at the levels of both gene and protein expression.…”
Section: Thyroid and Role Of Cytokinessupporting
confidence: 77%
“…Previous reports have demonstrated a positive correlation between ICAM-1 RNA and protein expression levels and the aggressive potential of PTC (25, 26), constituting ICAM-1 as a biomarker and a potential target for therapeutic interventions in thyroid cancer. PTCs are most commonly driven by two mutually exclusive somatic mutations, BRAF V600E or mutated RAS (29).…”
Section: Resultsmentioning
confidence: 94%
“…Moreover, clinical trials support the safety and tolerability of targeting ICAM-1 using monoclonal antibodies (20–24). Previous studies have shown that ICAM-1 expression is highly correlated with both the malignancy and metastatic status of thyroid tumors, as well as the V600E BRAF (BRAF V600E ) mutation (25, 26). The stark correlation between ICAM-1 expression and adverse prognostic outcomes in thyroid cancer patients suggests that ICAM-1 may serve as a therapeutic target for advanced, recurrent thyroid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…A previous profiling study revealed similar altered mechanisms, where overexpressed genes were related mainly to cell adhesion processes, protease binding, or ECM-receptor interactions [25]. ICAM-1 (Intercellular adhesion molecule 1) is an important molecule that has an important role in cell adhesion regulation and in the inflammatory response progression [26]. It was previously proven that ICAM-1 is upregulated in both classical and tall-cell PTC, therefore it could be considered a biomarker of PTC progression [26].…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 (Intercellular adhesion molecule 1) is an important molecule that has an important role in cell adhesion regulation and in the inflammatory response progression [26]. It was previously proven that ICAM-1 is upregulated in both classical and tall-cell PTC, therefore it could be considered a biomarker of PTC progression [26].…”
Section: Discussionmentioning
confidence: 99%